Arduino Radar Prototype Using Ultrasonic Sensor With C++ & Java Script Programming - Bobi Karomah; Dewi Sartika (Journal of Educational Engineering and Environment, 2025)
Radar is a tool that functions to detect the presence of objects around it. The role of the Arduino Radar Prototype is expected to facilitate tracking the presence of foreign objects. The radar prototype uses an ultrasonic sensor with Arduino that can detect objects and measure their distance. This study uses C++ and JavaScript programming which functions to process ultrasonic sensor data and display the results on the screen. Arduino IDE c++ & JavaScript software is used as a graphical programming tool that can display object detection read by the ultrasonic sensor. The results of this study are that the ultrasonic sensor is able to detect objects within a distance of 10-20 cm and is able to reach an angle of 30 to 90